Dynamics of branched tissue assembly - Manivannan, Sriram (BioMed Central, 2012)
The assembly of cells into tissues is a complex process controlled by numerous signaling pathways to ensure the fidelity of the final structure. Tissue assembly is also very dynamic, as exemplified by the formation of branched organs. Here we present two examples of tissue assembly in branched systems that highlight this dynamic nature: formation of the tracheal network in Drosophila melanogaster and the ducts of the mammary gland in mice. Extension of the branches during tracheal development is a stereotyped process that produces identical organ geometries across individuals, whereas elongation of the ducts of the pubertal mammary gland is a non-stereotyped process that produces unique patterns. By studying these two organs, we can begin to understand the dynamic nature of development of other stereotyped and non-stereotyped branching systems, including the lung, kidney, and salivary gland.